Manufacturing decision support systems - Parsaei, H. R.; Kolli, Sai; Hanley, Thomas R. (Manufacturing systems engineering series (Chapman & Hall), 1997)
"Manufacturing Decision Support Systems provides a forum for research and applications dealing with the design, development and implementation of decision support systems in the manufacturing domain. The book brings together contributions from leading experts in the field. It will appeal to all those concerned with decision support for manufacturing."--BOOK JACKET.